The Geometry of Aquifer System in the North Lower Slope of Bromo Volcano, East Java, Indonesia - Putra, Doni Prakasa Eka (2013)
Groundwater resources is categorized as an important and renewable resources, and use for a lot of purposes. Nowadays, it is globally understand that groundwater is under threat of degradation due to an appropriate use and should be managed carefully to achieve its sustainable use for the future generations. The north slope of Bromo Volcano in the East Java, Indonesia, is known with the high productivity aquifer area. In this region, there are a lot of springs and one of them has water discharge > 5000 L/s called as Umbulan spring. Besides, most of the people in this regions drill their own deep well to fulfill their need of water for household purposes, agricultures, commercials and industries. Therefore, necessary action should be taken in order to sustain the use of groundwater in this area. A vital tool to good groundwater management is a well-conceived understanditrg of the geometry aquifer system and this can be done by conducting surface observation which supported by the geo-electrical measurement in this area. Almost 100 measurements of vertical profiling using Schlumberger method were conducted and a fence diagram of sub-surface lithology succession can reveal. From the fence diagram, it is found that the aquifer system on this region are developed by four multi layers aquifers (unconfined to confined aquifer) of sandstone, sand and gravel, which hydraulically connected each other on some local area and the basement of the aquifer is defined to be tertiary volcaniclastics rocks. Following the regional flows of groundwater, the thickness of the aquifers is increased in the central part up to 200 m and decrease to the sea direction to less than 100 m. It is also recognized that in the regions, the most existing deep wells were abstract water mainly from the middle aquifer layers, which become the reason of the decreasing of the artesian water level.